Sisi Gelap Allah dalam Kitab Ayub - Sia Kok Sin (SOLA GRATIA: Jurnal Teologi Biblika dan Praktika, 2022)
Abstract:  A careful reading of the book of Job will reveal the dark side of God. God acted as if it were against His nature. God is merciful and kind, but he is the cause of Job’s suffering and does not provide answers to Job’s questions about the reason for his suffering. Some experts discuss this, but others ignore it. Through examining the book of Job, the author tries to explain the dark side of God in the book of Job. The author divides the book of Job into several parts, namely Job 1-2, 3-37, 38-41 and 42, as a basis for discussion and seeks to provide a theological review of God’s attitude and character towards Job in dealing with his suffering, interaction with his friends, or even with God himself. God was willing to “bet” with Satan, thus bringing tragedy in the life of Job, a godly man. God was silent totally in the midst of the theological debates of Job and his friends. God who spoke through His wisdom and omnipotence yet did not answer Job’s questions about the reasons for the tragedy in his life. Instead, God restored Job with his partial compensation. This article aims to remind readers of the dark side of God that will remain a mystery. The believer has to embrace this dark side of God with a faith that is not based on knowledge, feelings and experience but a total commitment to God. Total trust in God regardless of everything God allows to happen in his life. Abstrak: Pembacaan yang teliti terhadap kitab Ayub akan menghadirikan sisi gelap Allah. Allah bertindak seolah-olah bertentangan dengan natur-Nya. Allah yang maha murah dan baik justru yang menjadi penyebab penderitaan Ayub yang saleh dan tidak memberikan jawaban atas pertanyaan Ayub tentang alasan penderitaannya. Ada ahli yang membahas hal ini, tetapi ada ahli yang mengabaikannya. Melalui penyelusuran kitab Ayub penulis berupaya memaparkan sisi gelap Allah dalam kitab Ayub. Penulis membagi kitab Ayub menjadi beberapa bagian, yaitu Ayub 1-2, 3-37, 38-41 dan 42 sebagai dasar pembahasan dan berupaya memberikan tinjauan teologis sikap dan karakter Allah terhadap Ayub dalam menghadapi penderitaannya, interaksi dengan teman-temannya, atau bahkan dengan Allah sendiri. Allah yang mau “bertaruh” dengan Iblis, sehingga membawa tragedi dalam kehidupan Ayub, seorang yang saleh. Allah yang membisu di tengah perdebatan teologis Ayub dan teman-temannya. Allah yang berbicara melalui hikmat dan kemahakuasaan-Nya, namun tidak memberikan jawaban atas pertanyaan Ayub tentang alasan tragedi dalam hidupnya. Allah yang memulihkan Ayub dengan kompensasi parsialnya. Artikel ini bertujuan untuk mengingatkan pembaca akan sisi gelap Allah yang akan tetap menjadi suatu misteri. Hal ini perlu disikapi oleh orang percaya dengan iman yang tidak didasarkan atas pengetahuan, perasaan dan pengalaman, tetapi pada komitmen total kepada Allah. Kepercayaan total kepada Allah terlepas dari segala hal yang Allah izinkan terjadi dalam kehidupannya.